Analysis of Student Difficulty in Understanding the Roots of Nonlinear Equations - Rachmatin, Dewi; Sujana, Atep (International Conference on Elementary Education, 2022)
Mathematics is considered one of the hard lessons by some students, so needs to be analysed the difficulties faced by students as prospective teachers. This research aims to explore the problem of students mathematics study program in studying roots of nonlinear equation. The method used in this study was descriptive of the skin. The instrument was used in the form of a tertius test in the form of multiple choices consisting of 5 questions. The results showed that 68 students obtained an average score of 30.88; the highest value is 80, and the lowest value is 0. The results of the analysis of the answer are known that students still do not understand correctly the basic principles of iterative methods that have been studied, this is evident from the questions asked about the advantages and disadvantages of each iterative methods, as well as from fundamental questions about the basic principles for each iterative method that has been studied.